Effect of environmental regulated water temperature variations on survival, growth performance and haematology of African catfish, Clarias gariepinus (Our Nature, 2017)
A 56 day study was carried out to evaluate effect of temperature changes on survival, growth performance and haematology of Clarias gariepinus fingerlings fed housefly maggot meal (magmeal) diet. Ninety (90) Clarias gariepinus fingerlings, (initial mean weight 4.33±0.03g) were subjected to different environmental regulated temperature conditions in three locations (laboratory, outdoor, greenhouse). The observed average temperature was 26.53±0.01°C, 26.06±0.01°C and 31.52±0.00°C for laboratory, outdoor, greenhouse, respectively. Ten fingerlings stocked per experimental tank were fed in triplicates at 5% body weight in two portions per day. It was observed that different water temperatures affected fish growth. All experimental fish in the greenhouse died after 8 days of exposure. This happened around 14.00 hrs when water temperature reached 40°C. There was no significant difference (P0.05). The result confirms that Clarias gariepinus fingerlings reared at a mean temperature of 26°C (within the recorded optimal temperature range for good growth) performed well. Clarias gariepinus fingerlings are not able to survive when water temperature reaches to 40oC.